THE SEPARATIST RELIGIOUS EDUCATION IN UGANDA: AN UNHEALTHY APPROACH TO INTERRELIGIOUS DIALOGUE AND EXTREMISM - Bweyale, Josephine (Advances in Social Sciences Research Journal, 2018)
Abstract Interreligious dialogue is one of the potential approaches to help societies overcome differences and resolve religious conflicts. The majority of Uganda’s population constitutes different sects of Christians and Muslims. While currently, there may not be severe religious conflicts to raise alarm in Uganda; there are cases of religious intolerance that may culminate into religious terrorism. Religious intolerance is a fertile ground for religious fundamentalism and extremism. Whilst education has been recommended as a potential to discourage and combat religious terrorism, the approach to religious education in Uganda may instead breed religious terrorist tendencies. The article is a culmination of documentary analysis of several documents including the national educational and syllabus. These documents spell out the goals, objectives and the subject content.